Sensory Evolution and Ecology of Early Turtles Revealed by Digital Endocranial Reconstructions - Lautenschlager, Stephan; Ferreira, Gabriel S.; Werneburg, Ingmar (Frontiers in Ecology and Evolution, 2018)
In the past few years, new fossil finds and novel methodological approaches have prompted intensive discussions about the phylogenetic affinities of turtles and rekindled the debate on their ecological origin, with very distinct scenarios, such as fossoriality and aquatic habitat occupation, proposed for the earliest stem-turtles. While research has focused largely on the origin of the anapsid skull and unique postcranial anatomy, little is known about the endocranial anatomy of turtles. Here, we provide 3D digital reconstructions and comparative descriptions of the brain, nasal cavity, neurovascular structures and endosseous labyrinth of Proganochelys quenstedti, one of the earliest stem-turtles, as well as other turtle taxa. Our results demonstrate that P. quenstedti had retained a simple tube-like brain morphology with poorly differentiated regions and mediocre hearing and vision, but a well-developed olfactory sense. Endocast shape analysis indicates that an increase in size and regionalization of the brain took place in the course of turtle evolution, achieving an endocast diversity comparable to other amniote groups. Based on the new evidence, we further conclude that P. quenstedti was a highly terrestrial, but most likely not a fossorial taxon